Estudio de la familia Formicidae, en la micro cuenca del río Yungañan. (Formación vegetal bosque) en La Maná. Cotopaxi 2021. - Auquilla Cruz, Jhonatan Israel (2021)
The purpose of this research is to study the impacts of anthropogenic (human) causes on the tropical forest, in the entomofauna of the Formicidae family, in the micro-basin of the Yungañan River. (Forest vegetation formation), divided into three transects, each study surface is evaluated in one ha, divided into 20 random samplings each. The objective of this research is to identify the diversity and abundance of the entomofauna of the Formicidae family, existing in the forest plant formation. Applying the construction method of “garbage sieve”, or litter (Carbonell 2004), and attractants with baits (Corrales-Moya and Hanson 2017). The samples obtained were classified and identified in the entomology laboratory, using dichotomous keys; conservation measures are subsequently applied. In the analysis of the diversity of ants, it was carried out by means of tables and dynamic graphs of percentages, finding, 5 subfamilies, 14 genera, belonging to the representative groups; Epigean hunters, nomadic hunters, Epigean omnivores, arboreal foragers, atinas, leaf cutters. Determining that the more an area is intervened by man, the amount of diversity of ants is less.